Restrained step triple connected domination number of a graph. (4th July 2019) - Mahadevan, G.; Suganthi, M. Vimala; Basira, A. Iravithul
Abstract: In this paper, we introduce the new parameter called restrained step triple connected domination number of a graph. A set S ⊆ V of a graph G is said to be restrained step triple connected dominating set, if < S > is the restrained triple connected dominating set and < V – S > is a perfect matching. The minimum cardinality taken over all the restrained step triple connected dominating sets is called the restrained step triple connected domination number of G and is denoted by γrstc ( G ). In this paper we investigate this parameter for some standard classes of graphs, special types of graphs, and some product related graphs.